2017
DOI: 10.1038/eye.2017.290
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal retinal imaging in central serous chorioretinopathy treated with oral eplerenone or photodynamic therapy

Abstract: PurposeTo correlate function and structural optical coherence tomography (OCT) to optical coherence tomography angiography (OCT-A) measures in patients affected by central serous chorioretinopathy (CSC) and to describe their changes after treatments (ie oral eplerenone, half-fluence photodynamic therapy (PDT)).Patients and methodsTwenty eyes of 16 consecutive patients with treatment-naïve CSC undergoing either eplerenone or PDT were enrolled in this prospective, observational study. All patients underwent stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
1
23
0
2
Order By: Relevance
“…As recently reported, oral eplerenone treatment does not affect choriocapillaris density, similarly to our findings [6,25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As recently reported, oral eplerenone treatment does not affect choriocapillaris density, similarly to our findings [6,25].…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have reported vessel density modifications mainly of DCPD, probably related to mechanical displacement of retinal vessels caused by SRF. In CCSC eyes, due to the pathogenesis of the disease typically involving choroid and outer retinal layers, DCP vessel density reduction after eplerenone was not statistically significant [25]. Similarly, OCTA analysis in our sample showed no chorioretinal vascular changes after the systemic therapy.…”
Section: Discussionmentioning
confidence: 55%
“…Full or half-fluence photodynamic therapy (PDT) still plays a key role in the treatment of CSC in order to reduce choroidal hyperpermeability. Several studies have confirmed the efficacy of PDT, showing a reduction in serous retinal detachment and a decrease in choroidal thickness, but the safety effects are still debated over the long term [ 27 32 ]. Intravitreal anti-vascular endothelial growth factor (VEGF) agents have been given to reduce vascular permeability, although the exact role of VEGF in the pathogenesis of CSC is still unclear [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some instruments use their own proprietary software, these include Cirrus (AngioPlex software, Carl Zeiss Meditec, Inc., Dublin, CA, USA), [ 5 , 10 ] AngioVue software (Optovue, Inc., Fremont, CA, USA), [ 11 , 12 ] and RS -3000 Advance (Nidek, Gamagori, Japan). [ 6 ] In the majority of the studies, however, images are exported and post-processed with a variety of different thresholding methods, including fixed cutoffs, [ 13 15 ] dynamic cutoff (e.g., mean, [ 9 , 16 , 17 ] ImageJ [National Institutes of Health, Bethesda, MD] default algorithm, [ 18 ] Otsu’s algorithm), [ 19 , 20 ] prototype software, [ 21 , 22 ] and more complex methods combining preprocessing filters and multilevel thresholds strategies. [ 23 26 ] It is still uncertain whether different algorithms lead to the same or, at least, similar results and findings from many studies could have been influenced by the algorithm utilized.…”
Section: Introductionmentioning
confidence: 99%